Hubungan Kekuatan Otot Perut, Punggung, Tungkai, dan Kelenturan Otot Punggung Terhadap Teknik Bantingan Pinggang Atlet Gulat Grobogan - Rizky Fajar Fadila; Ranu Baskora Aji Putra; Bambang Priyono; Adi S (Indonesian Journal for Physical Education and Sport, 2024)
The research was motivated by the fact that there are new wrestling athletes, and athletes who have not done training for a long time, where they have difficulty in doing waist slams due to lack of body flexibility and strength problems. The research aims: (1) Knowing the relationship between abdominal muscle strength, back, legs and back muscle flexibility to waist slams in wrestling athletes, (2) Knowing the level of abdominal muscle strength, back, legs and back muscle flexibility to waist slams in wrestling athletes. The research design is quantitative using the "Correlational design". The population in this study were Grobogan Regency wrestling athletes. The sample in this study were 18 Grobogan Regency wrestling athletes aged 18-25 years. The instrument used in the assessment is a measurement test. Processing and analysis techniques using prerequisite tests and hypothesis testing. The results showed: (1) There is no significant relationship between abdominal muscle strength in performing waist slamming techniques. (2) There is a significant relationship between back muscle strength in performing waist slam techniques. (3) There is no significant relationship between leg muscle strength in performing the waist slam technique. (4) There is a significant relationship between the flexibility of the back muscles in performing the waist slam technique. (5) There is a relationship between the strength of the abdominal muscles, back, legs, and the flexibility of the back muscles and the ability to waist slam.